Single Input Fuzzy Logic Controller for Liquid Slosh Suppression - Mohd Tumari, Mohd Zaidi; Saat, Shahrizal; Kasno, Mohamad 'Afif; Johal, Muhammad Syahrani; Bahari, Muhamad Falihan; Ahmad, Mohd Ashraf (International Journal of Electrical Engineering and Applied Sciences (IJEEAS), 2019)
The chaotic nature of liquid slosh and the complex fluid dynamic motion in the container makes the traditional model-based control techniques complex and difficult to synthesize in practice. This paper presents investigations into the development of single input fuzzy logic controller (SIFLC) for liquid slosh control. The proposed approach, known as the SIFLC, reduces the conventional two-input FLC (CFLC) to a single input single output (SISO) controller. Two parallel SIFLC are developed for both lateral tank position and liquid slosh angle control. With the purpose to confirm the design of control scheme, a liquid slosh model is considered to represent the lateral slosh motion. The performances of the control schemes are accessed in terms of lateral tank tracking capability, level of liquid slosh reduction and time response specifications. Supremacy of the proposed approach is shown by comparing the results with hybrid model-free Fuzzy-PID controller with derivative filter (PIDF). Finally, it is seen from the simulation results that the proposed control scheme has able to reduce the liquid slosh without unambiguously model the liquid slosh behavior.